SEMIOTIC ANALYSIS OF “KIM JONG UN AND DONALD TRUMP” CARTOON - Sabam Simandalahi; Ray Josua Putra Sidabutar; Arsen Nahum Pasaribu (Jurnal Education and Development, 2022)
This research paper focuses on examining the meaning and examining the types of signs used in the cartoons of Kim Jong Un and Donald Trump. The researcher sees that the cartoon images devoted to these two characters are very interesting because they have their own semiotic meaning. This picture is a dilator behind the existence of a dispute between the two. The data taken are interesting pictures of the authors sourced from the internet. The research method uses qualitative research methods that explain the meaning and types of signs used following the theory of Charles Sanders Pierce. The results of the research are The general meaning of Semiotic Analysisof Kim Jong Un and Donald Trump Cartoon is generally the competitive nuklir of each other… the competitive is to make each other down diplomacy and to make a better nuclear. The general meaning of this research is they learn and in their thinking is to make better nuclear to make each other scared of him.The general kind of sign in this paper is Iconic sgn. The iconic sign is to show the reader about similar object. Similar of each other is the first, second, third, and fifth picture. The same sign of Kim Jong Un and Donald Trump is shows. The first image is they same to learn better of nuclear. Second picture they are same in the television program. Third and fifth they are have a same mindset, to against each other